Case study: A qualitative study aimed at comparing standard therapy in a breast cancer patient to the spiritual healing and psychological support, in improving patient's compliance - Ali Hassan; Hafiz Abdul Majeed; Azizullah Kakar (AMMANIF, 2021)
Background: Breast tumor is the most well-known type of cancerous growth in ladies of Pakistan. The effect of the underlying diagnosis, treatment conventions, chemotherapeutic agents in contrast with culture, social and psychological parts of the ailment is not settled. Method: This subjective review analyzed and contrasted the standard treatment conventions and the Spiritual Healing including psychological support utilized by patient with breast cancer in connection to its effect on the enhanced quality of her life and her enhanced wellbeing status. Mrs Fouzia Mohsin a patient with bosom malignancy persistent, mother of 6 youngsters having an age of 53 years and 5 months from Faisalabad experiencing chemotherapy from Shifa International Hospital Islamabad and also Spiritual Healing and mental support was met. Information were dissected utilizing topical examination. The patient's understanding of bosom disease concentrated on the conviction of suitability of medication treatment picked by her physician and in addition the positive mental impact of Spiritual recuperating alongside the scope of feelings felt all through her ailment. Results: The significance of spiritual healing and mental support of the family along with breast cancer tackling techniques i.e chemotherapy, radiotherapy and mastectomy is far excessively helpful and steady in method for upgrading consistence to treatment and accordingly enhanced personal satisfaction. This is the principal study to look into the case of lady experiencing breast cancer on the experiencing chemotherapy and Spiritual Healing. This article gives illumination of the voiced encounters of a woman with breast tumor. The information not just highlights the part of standard chemotherapy and radiotherapy as fundamental adapting methodologies additionally underlines the adapting of issues like disengagement, hostility, and outrage as regular reactions to chemotherapy through Spiritual Healing and Psychological support of the family. Conclusion: One of a kind elements are bosom malignancy patient's have to look for Spiritual Healing and Support of family for her sickness to remain spurred and increment in her consistence. These social elements require advance examination and research.